Evangelical, charismatic and pentecostal in Israel: local politics and global relevance - Kirchner, Anna Maria (PentecoStudies, 2019)
Among Arab Christians in Israel there is an intense dispute about identity, which is tangible in the use of names such as "Evangelical", "Charismatic" and "Pentecostal". By understanding these names as local political considerations, this paper shows how and why these names are used or rejected. In 2005, the Association of Baptist Churches, Church of the Nazarene, Assemblies of God and Open Brethren, as well as several para-church institutions, united as the Convention of Evangelical Churches in Israel. This Convention represents the context Arab Evangelicals find themselves in: between a local, mostly Catholic and Orthodox Christianity and global Evangelicalism. In this global-local entanglement, the name "Evangelical" emerges. Meanwhile a "Pentecostalization" or "Charismatization" can be seen in almost all the churches, these churches feel uncomfortable with both these designations even though "Charismatic" is less vehemently refused compared to "Pentecostal" as self-designation. Rather, "Evangelicals" exclude those within their circles who promote strong Charismatic actions as "Pentecostals", in order not to endanger their fragile position within the broader Christian community in Israel.